Normative Juridical Analysis of the Validity of Regulations on the Establishment of Merah Putih Village Cooperatives in the Perspective of the Hierarchy of Laws and Regulations in Indonesia - Elfiani, Fitri (Dinasti Research, 2026)
This study aims to analyze the legal validity of the regulations governing the establishment of the Merah Putih Village Cooperative within the framework of the hierarchy of laws and regulations, as well as to examine normative disharmony between cooperative law and village governance regulations. This policy is driven by Presidential Instruction No. 10 of 2025, supported by Ministerial Regulations of Village Affairs and the Ministry of Finance concerning the use and management of village funds, which raises juridical issues related to legitimacy and regulatory authority. This research employs a normative legal method using statutory and conceptual approaches. Legal materials are analyzed qualitatively through legal interpretation to assess the conformity of norms within the legal system. The results indicate that although the regulations have a strategic objective in strengthening the village economy, they remain juridically problematic. The Presidential Instruction does not have generally binding legal force, while ministerial regulations are limited in scope and cannot establish new legal norms. Vertical disharmony with the Village Law and horizontal disharmony among regulations on village funds are also identified, potentially leading to legal uncertainty in policy implementation. This study concludes that regulatory harmonization and stronger legal foundations are necessary to ensure clear legitimacy in the establishment of village cooperatives.